2017
DOI: 10.1039/c7cp04047d
|View full text |Cite
|
Sign up to set email alerts
|

Accurate experimental and theoretical enthalpies of association of TiCl4 with typical Lewis bases used in heterogeneous Ziegler–Natta catalysis

Abstract: Adducts of TiCl with Lewis bases used as internal or external donors in heterogeneous Ziegler-Natta (ZN) catalysis represent a fundamental interaction contributing to the final composition of MgCl supported ZN-catalysts. This study presents the accurate experimental evaluation, from titration calorimetry, of the formation enthalpy of TiCl adducts with 15 Lewis bases of industrial interest. In addition, we report the accurate energies of association of TiCl with the same Lewis bases from calculations at the DLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 81 publications
2
23
1
Order By: Relevance
“… 61 Previous works showed that the B3LYP-D3 method provides reliable results for structures, thermochemistry, and kinetic activation parameters for Pt(II) complexes. 38 , 39 , 62 65 The Def2SVP basis set 66 , 67 for all atoms was employed with relative effective core potential for the platinum atom. The solvent has been introduced as polarizable continuum (PCM).…”
Section: Models and Methodsmentioning
confidence: 99%
“… 61 Previous works showed that the B3LYP-D3 method provides reliable results for structures, thermochemistry, and kinetic activation parameters for Pt(II) complexes. 38 , 39 , 62 65 The Def2SVP basis set 66 , 67 for all atoms was employed with relative effective core potential for the platinum atom. The solvent has been introduced as polarizable continuum (PCM).…”
Section: Models and Methodsmentioning
confidence: 99%
“…For better accuracy, we have performed single point calculations using PBE0 functional, [66] TZVP basis set, [62] and dispersion correction (DFT‐D3) [63] . Our choice of the PBE‐D3/TZVP//PBE0‐D3/TZVP level of theory is based on benchmarking and computational studies [67,68,34] . For the calculations that we have performed, the energy convergence criteria was 10 −6 H, and the norm for the cartesian gradients was 10 −3 .…”
Section: Methodsmentioning
confidence: 99%
“…Adsorption energies were obtained using DFT calculations with the B3LYP-D3 functional [46]. This functional has been proven by Cavallo et al [47] to well reproduce the experimental association energies between TiCl4 of fifteen electron donors. The LANL2DZ effective core potentials (ECP) function and basis set were used for Ti atom [48], while the 6-31G(d,p) basis set was used for others.…”
Section: Adsorption Modesmentioning
confidence: 99%